Advances in gear design and manufacture - Radzevich, S. P. (Stepan Pavlovich) (Boca Raton : CRC Press, 2019)
Advances in Gear Design and Manufacture deals with gears, gear transmissions, and advanced methods of gear production.The book is focused on discussion of the latest discoveries and accomplishments in gear design and production, with chapters written by international experts in the field. Topics are aligned to meet the requirements of the modern scientific theory of gearing, providing readers precise knowledge and recommendations on how perfect gears and gear transmissions can be designed and produced, and how they work. It explains how gears and gear transmissions can be designed to reach high a "power-to-weight "ratio, and how to design and produce compact, high-capacity gearboxes.
OCLC-licensed vendor bibliographic record.
Keywords: Gearing -- Design and construction; TECHNOLOGY & ENGINEERING / Mechanical; TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Industrial Design / General